Health Behavior of Abuan Village Community: Social Dimension Review - Mahendra Bhandesa, Asthadi; Indrayoni, Putu; Kartiningsih, Ni Luh Putu (Udayana Journal of Social Sciences and Humanities; Vol 3 No 1 (2019): UJoSSH, Feburary 2019, 2019)
The development of health is basically an effort to increase awareness, willingness, and the ability of every person to commit a healthy life to achieve the highest level of public health. Health behavior is influenced by several factors including physical, mental, spiritual, and social. This study aims to gain clarity about the social dimensions of the health behavior of the people of Abuan Village, Kecut, Bangli. Data collection in this research using observation, interview, and document study technique. Furthermore, the technique of data analysis is through data reduction or chosen according to research purpose. In the process of data analysis carried out throughout the study or carried out continuously from the beginning to the end of the study. Through the process of systematically tracking and arranging interview transcripts, field notes, and other materials, showed that the social dimension of health behavior in the form of a) human relationship with God; b) human relationships with humans; and c) human relationships with the environment.